PertanggungJawaban Pidana Terhadap Dokter Atas Kesalahan Diagnosis Secara OnlinePada Klinik Kecantikan Online - Regitamara Delfirani Rosa; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The percentage of errors diagnosed by doctors to patients in online clinics, it is one of the challengesthat must be faced for advancement in the health sector. A study conducted by the association of trial lawyerof America shows that the percentage of doctors misdiagnosed is as much as two percent of the totalpatients who undergo examinations in the clinic. Patients who are misdiagnosed usually have atypicalsymptoms that make diagnosis more difficult. If a diagnosis error by a doctor occurs, the doctor should orcan be held accountable, because in general everyone is responsible not only for the loss caused by hisactions, but also for losses caused by negligence or inadvertence.The formulation of the problem in this research is, first, how is the online clinic's legal positionbased on the Law of the Republic of Indonesia Number 36 of 2009 concerning Health? second, how is thecriminal responsibility against doctors based on the Law of the Republic of Indonesia Number 29 of 2004concerning Medical Practices?The research is a normative legal reseach. From the results of the problem research there are twomain things that are collected, first, the position of online clinical criminal law in the provision of healthservices is based on the Law of the Republic of Indonesia Number 36 of 2009 concerning Health that everyperson has the right to obtain safe, quality and affordable health services. Second, the accountability ofcriminal law against doctors is based on the Law of the Republic of Indonesia Number 29 of 2004concerning Medical Practices, namely if a doctor commits a mistake made by a doctor or other healthworker which causes damage or disability in the victim's body negligently.Keywords:criminal liability, diagnosis, health services